The family of Pa-di-Amun-neb-nesut-tawy from Thebes (TT 414) revisited : the case study of Kalutj/Nes-Khonsu (G108 + G137) - Budka, Julia, (Archaeopress Egyptology ;, 2022)
This text identifies a key figure in the family that reused the Saite tomb of Ankh-Hor (TT 414) in the Asasif: Kalutj/Nes-Khonsu. Examining the funerary assemblage revealed not only details of Late Dynastic and Ptolemaic burial customs in Thebes but also additional information on the priesthood of Khonsu and of the sacred baboons in this era.